Women's Emancipation in Their Contribution to Economic Development in the Surakarta Residency Region 2016-2020 - Ririn Maela Sari; Muhammad Arif (Prosiding University Research Colloquium, 2022)
Gender refers to the relationship between men and women and how these social relationships are constructed. Gender inequality occurs in all aspects of life. The results of human development do not provide equitable benefits between men and women and have not been effective enough in increasing women's development achievements in the fields of education, employment and the economy. Gender inequality in rights, resources, and political access not only harms women in general but also harms members of society as well as hinders development. Low gender equality will limit productivity, economic growth and reduce overall development efficiency. This study aims to determine the effect of the gender development index, gender empowerment index, women's involvement in parliament, the average length of schooling for women and the number of female civil servants on economic development in the Surakarta residency area in 2016-2020. This study uses secondary data with panel data regression analysis. Panel data is a combination of cross section and time series data. The model chosen in this study is to use the Fixed Effect Model (FEM) method after performing the Chow test and Hausman test. The results of this study indicate that simultaneously the variables of the gender development index, gender empowerment index, women's involvement in parliament, the average length of schooling for women and the number of female civil servants have an effect on economic growth. Partially, the gender development index variable has a negative and insignificant effect, the gender empowerment index has a positive and insignificant effect, the involvement of women in parliament has a positive and insignificant effect, the average length of schooling for women has a negative and significant effect, and the number of female civil servants has a negative effect. and significant to economic growth.